Bounce! The Wonderful World of Rubber - Schreyer, Karmel (New YORK Cambridge University Press, 2014)
It's in our shoes, cars, bikes, golf balls, clothing, kitchens$1! =(Bwhat would we do without rubber? Learn about where rubber comes from, how we use it, and how we depend on it more and mores
Keywords: English language Textbooks for foreign speakers; Readers (Elementary); Textbooks for foreign speakers; Readers (Adult)